Evaluation of Sensitivity to Phoxim and Cypermethrin in an Endoparasitoid, Meteorus pulchricornis (Wesmael) (Hymenoptera: Braconidae), and Its Parasitization Efficiency Under Insecticide Stress. Issue 1 (5th February 2021) - Sheng, Sheng; Wang, Jiao; Zhang, Xiao-rui; Liu, Zhi-xiang; Yan, Meng-wen; Shao, Ying; Zhou, Jin-cheng; Wu, Fu-an; Wang, Jun
Abstract: Insecticides can have consequences for beneficial arthropods. Insect parasitoids can contact insecticides through direct exposure spray droplets or residues on crop foliage. Here, we focus on better understand the response of Meteorus pulchricornis (Wesmael), a parasitoid wasp of lepidopteran pests, and its detoxification mechanisms on stress caused by phoxim and cypermethrin. Hence, we determined the dose–mortality curves and estimating the sublethal concentrations (LC30 and LC50 ). Then, we applied the sublethal concentrations against adult parasitoids to assess its survival, parasitism efficacy, and also developmental and morphometric parameters of their offspring. Simultaneously, we check the activities of glutathione S -transferase (GST), acetylcholinesterase (AChE), and peroxidase (POD) after sublethal exposure of both insecticides, which has measured until 48 h after treatment. Overall, phoxim and cypermethrin exhibited acute lethal activity toward the parasitoid with LC50 values 4.608 and 8.570 mg/liter, respectively. Also, we detect that LC30 was able to trigger the enzymatic activity of GST, AChE, and POD, suggesting a potential detoxification mechanism. However, even when subjected to sublethal exposure, our results indicate strong negatives effects, in particular for phoxim, which has affected the parasitism efficacy and also the developmental and morphometric parameters of M. pulchricornis offspring. Therefore, it can be concluded that both phoxim and cypermethrin have negative impacts on M. pulchricornis and we suggest cautioning their use and the need for semifield and field assessments to confirm such an impact.